South Pole ice core total air content - Sowers, Todd A. (IEDA: US Antarctic Program Data Center, 2019)
The total air content in ice core samples are a fundamental indication of the multitude of processes that impact densification of snow in polar regions. In addition, variations in the elevation of the ice sheet directly control the pressure in the bubble close off region and thereby the total gas content. Attempts to remove the physical factors (temperature, accumulation rate, dust content, seasonality) impacting the total air content could provide a means of assessing variations in the elevation of the South Pole over the last 50,000 years.